Framework for the Reform of Education Systems and Planning for Quality - Patrinos, Harry Anthony; Velez, Eduardo; Wang, Catherine Yan (World Bank, Washington, DC, 2014)
In 2000, the goal that, by 2015, all children will have access to, and complete, free and compulsory primary education of good quality, was set. Despite the progress in terms of student enrollment and completion, the quality of learning produced in developing countries remains poor. Existing models of education production are inadequate for informing education reform for the purpose of improving school quality, as measured by student learning. Thus, a broader and more integrated approach of policy making is put forward. Building on theory and empirical evidence on what works, the paper puts forward a framework for improving the quality of education. The framework includes six factors: (1) assessment; (2) autonomy; (3) accountability; (4) attention to teachers; (5) attention to early childhood development; and (6) attention to culture. Going forward, there is a need to develop a system of international quality benchmarks drawing on a larger body of evidence. Most importantly, more empirical evidence from impact evaluations is needed.